Addressing water, food and poverty problems together--Methods, tools and lessons - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
This sourcebook entitled “Addressing water,food and poverty problems together: Methods,tools and lessons” is part of a wider process to capitalize on results from the Phase 1 of CPWF (2004-2008). Phase 1 of CPWF cast its net widely. Sixty-eight individual research projects were carried out in ten river basins around the world. The learning was immense. Unfortunately, many Phase 1 lessons and experiences are locked away in people’s minds or hidden in long technical and scientific reports that are difficult to access, particularly for non-researchers.